Agency Cost and Financial Performance of Listed Firms in Nigeria - Oyinkansola, Muritala Abdulafiz; Ebenezer, Ariyibi Mayowa; Ayanwale, Obadeyi James; Oludare, Asogba Israel (The Journal of Accounting and Management, 2025)
The overall financial performance of a corporate entity, has continually been affected by costs that is expended towards ensuring corporate alignment between the managers and owners of the firm. Knowing that these agency costs would aid the corporate attianment of shareholder maximization. This study examines into the impact of agency cost on financial performance of listed firms in Nigeria. The study conceptualized and empirical examined the impact of asset utilization (monitoring cost), audit fee (contracting cost) and operating ratio (bonding cost) on the return on equity (book-based measure) and earning per share (market based measure). The secondary data was sourced from audited financial statement of ten industrial companies and ten cosumer goods companies listed on the Nigeria stock exchange group from the period of 2019 to 2023. The findings from the GMM (Generalized Method of Moment) revealed for the objective one that asset utilization, Audit fee and operating expenses ratio has positive significant effect on return on equity. Objective two revealed that asset utilization, Audit fee has positive significant effect on earnings per share. It is therefore concluded that firms should prioritize improving asset utilization as a means of enhancing profitability.